Double magnetron cluster set-up for synthesis of micro and nano structure coatings - Yakovin, S.; Zykov, A.; Dudin, S.; Sergiec, M.; Farenik, V. (Вопросы атомной науки и техники, 2015)
In the present paper, the results studying the technological regimes of reactive magnetron sputtering in cluster set-up with two planar magnetrons, plasma source and medium energy ion source are presented. Magnetron current-voltage characteristics as well as dependencies of the magnetron current, voltage and the total pressure in the chamber on the reactive gas flow are presented with emphasis on the features of the joint work of the two magnetrons with targets of different materials using different reactive gases. The technological “window” is determined on the basis of the measured characteristics.